Near‐field scattering centre modelling for complex targets - Yanxi Chen; Kunyi Guo; Zhouyang Liu; Xinqing Sheng (IET Radar, Sonar & Navigation)
Abstract The parametric scattering centre (SC) model of the target has been widely used in the rapid simulation of radar image. Most of the existing SC models are suitable for far‐field scattering where the radar cross section (RCS) is independent of the distance from the target to the radar. However, when the electromagnetic scattering of the target is in the near‐field region of radiation, the RCS of the target changes dramatically in distance. The existing SC model cannot characterise these important near‐field characteristics. In this paper, the near‐field model with the dependence description of the SC on the distance is proposed. Firstly, the scattering characteristics of several main geometric structures of the extended target in the near‐field radiation region are analysed. Then, on the basis of far‐field SC model expressions, the description of the relationship between amplitude and phase of the SC model and distance is added. Finally, the correctness of the near‐field SC model is verified by comparing with the accurate full‐wave numerical method. In order to further illustrate the practicability of the near‐field SC model, an actual aircraft target is used. The results proved that the near‐field SC model has the advantages of high accuracy and high computational efficiency.